The Relationship Pattern Of Exclusive Breastfeeding And MP-ASI Against Stunting Incidence In Children Aged 6-24 Months In The Village Of Larangan, The Working Area Of Puskesmas Candi - Bella Dwi Kurnia Fitri; Taufiqurrahman Taufiqurrahman; Mujayanto Mujayanto (Journal of Nutrition Explorations, 2025)
It is known that the Candi Health Center working area which is the locus of stunting in 2022 is Larangan Village with a prevalence of 13.9%. To determine and analyze the relationship between exclusive breastfeeding and complementary feeding patterns and the incidence of stunting in 6-24 month old children in Larangan Village. Observational research, making observations of research subjects without intervening. Cross sectional design. The results showed that most of the newborns in Larangan Village who were not only breastfed were 44 newborns (64.6%), and 24 newborns who were exclusively breastfed (35.4%). The results of the study showed that 54 (79.5%) baduta in Desa Larangan had a non-standard complementary food feeding pattern, compared to 14 (20.5%) baduta with a non-standard complementary food feeding pattern. The results showed that 25 out of 68 baduta were stunted, which amounted to 36.7%. After being tested with chi square, there was an association between the history of exclusive breastfeeding and complementary feeding patterns with the incidence of stunting. It is expected to be an input, especially for the Larangan Village community, about the importance of a history of exclusive breastfeeding patterns and complementary feeding patterns to prevent stunting.